Model Pembelajaran Contextual Teaching and Learning (CTL) Dalam Meningkatkan Kualitas Pemahaman Materi Fiqih - Zaenal Abidin; Enung Nugraha; Wasehudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The background of this research is that there are still many teachers who still use the lecture method and practice questions when learning fiqh. Whereas in the 2013 curriculum students are required to be more active and critical. Thus, students feel bored and lack enthusiasm in participating in fiqh learning in class. For this reason, teachers need an effective and efficient learning model. The method used in this study is a qualitative descriptive method. The object of this research is all students of MTs Al Ulya Al Mubarok Serang City. The sample is inserted by theoretical technique. Data were collected using interview, documentation, and observation instruments. The results of the study on the effectiveness of the Contextual Teaching and Learning (CTL) learning model in improving the quality of understanding fiqh material at MTs Al Ulya Al Mubarok Serang City, that: (1) The Contextual Teaching and Learning (CTL) learning model in improving the quality of understanding fiqh material is sufficient. both in accordance with the objectives and components of the Contextual Teaching and Learning (CTL) learning model, it can be seen from the way the teacher delivers the material by inviting students to observe directly, then discuss, create study groups, and direct students to relate the material to real life (2) The effectiveness of Contextual Teaching and Learning (CTL) in improving fiqh material at MTs Al Ulya Al Mubarok Serang City, this learning is more meaningful and real, meaning that students are required to be able to capture the relationship between learning experiences at school and real life. However, the material he learns will be deeply embedded in students' memory, so it will not be easily forgotten